Apparent Molal Volumes and Apparent Molal Adiabatic Compressibilities of Digols in Water at Different Temperatures - Nagabhushan Raju, K.; Sailaja, D. (Asian Journal of Chemistry, 2010)
Apparent molal volumes (fv) and apparent molal adiabiatic compressibilities (fK) have been calculated from the measured densities for the binary liquid mixtures of digols namely diethylene glycol monomethyl ether (methyl digol-MD), diethylene glycol dimethyl ether (dimethyl digol- DD) and diethylene glycol monobutyl ether (butyl digol-BG) with water at 303.15, 308.15, 313.15, 318.15 and 323.15 K. The apparent molal volume data has been analyzed using Mason's equation and calculated the apparent molal volumes at infinite dilution (fvo), the slope values (Sv) and the apparent molal expansibilities (fEo = ¶fvo/¶T). From the measurements of ultrasonic velocity (u) and density (r) the apparent molal adiabatic compressibilities at infinite dilution (fko) and the experimental slopes (Sk) are computed. The analysis of the results indicates the presence of solute solvent interactions in these liquid mixtures and the solutes are found to be the structure makers in water and their structure making ability is in the order of methyl digol < dimethyl digol < butyl digol.